A Comprehensive Review of the Protein Subunit Vaccines Against COVID-19 - Heidary, Mohsen; Kaviar, Vahab Hassan; Shirani, Maryam; Ghanavati, Roya; Motahar, Moloudsadat; Sholeh, Mohammad; Ghahramanpour, Hossein; Khoshnood, Saeed (Frontiers in Microbiology, 2022)
Two years after severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), in ‎December 2019, the first infections were identified in Wuhan city of China. SARS-CoV-2 infection caused a global pandemic and accordingly, 5.41 million deaths worldwide. Hence, ‎developing a safe and efficient vaccine for coronavirus disease 2019 (COVID-19) seems to be an urgent need. Attempts to produce efficient vaccines inexhaustibly are ongoing. At present time, ‎according to COVID-19 vaccine tracker and landscape provided by World Health Organization (WHO), there are 168 vaccine candidates all over the ‎world. In between, protein subunit vaccines are types of vaccines that contain a viral protein ‎like spike protein or its segment as the antigen assumed to elicit humoral and cellular immunity and good ‎protective effects. Previously, this technology of vaccine manufacturing was used in a recombinant ‎ influenza vaccine (RIV4). In the present work, we review protein subunit vaccines passing their phase 3 and 4 clinical trials, population participated in these trials, vaccines ‎manufactures, vaccines efficiency and their side effects, and other features of these vaccines.‎